Improvement of the technology of meat products using calcium alginate gels - Pasichnyi, Vasyl; Yastreba, Yulia; Bilotserkivets, M. (My University, 2014)
Nowadays, improving of competitiveness of food products is connected with the improvement of consumer characteristics, by extending the range, by developing new technologies based on modern scientific and technological achievements.
Keywords: кальцій; альгінати; поліпшення якості; quality improvement; calcium; sodium alginate; кафедра технології м’яса і м’ясних продуктів